The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1159/000148246
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Bilateral Subthalamic Nucleus Stimulation in the Treatment of Parkinson’s Disease: Correlation with Intra-Operative Multi-Unit Recordings but Not with the Type of Anaesthesia

Abstract: Background: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) gained general acceptance in the treatment of Parkinson’s disease (PD). Objective: To study the clinical outcome and the predicting factors of efficacy of chronic STN stimulation, while DBS electrodes were implanted under local or general anaesthesia with intra-operative electrophysiological guidance based on multi-unit recordings. Methods: We included a large single-centre cohort of 54 patients with advanced PD (mean age: 59 years; dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 209 publications
2
46
1
Order By: Relevance
“…Lefaucheur et al [24] found no significant differences in clinical outcome in their retrospective analysis of bilateral STN DBS in 24 LA and 30 GA patients. The authors concluded that semi-microelectrode recordings and clinical outcomes were not adversely affected by the GA employed.…”
Section: Previous Reports Of Stn Dbs Under Gamentioning
confidence: 91%
See 2 more Smart Citations
“…Lefaucheur et al [24] found no significant differences in clinical outcome in their retrospective analysis of bilateral STN DBS in 24 LA and 30 GA patients. The authors concluded that semi-microelectrode recordings and clinical outcomes were not adversely affected by the GA employed.…”
Section: Previous Reports Of Stn Dbs Under Gamentioning
confidence: 91%
“…Groups that rely on neurophysiological recordings during surgery have adopted specific anaesthetic protocols [23][24][25][26]37] . Groups that rely on routine verification of lead location on immediate postoperative stereotactic imaging are less likely to be affected by performing surgery under GA [14,20,38,39] .…”
Section: Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A critical limitation in our understanding of anesthetic best practices is that only a few studies have quantified the effect of anesthetics on MER [14,41,44,45], although a number have qualitatively assayed it, suggesting that too much sedation degrades the MER quality [13,14,15,20,39,41,42,43,44,46,47,48,49,50,51,52,53,54]. Considering those studies that quantified the effects on MER, we do know that some were affected by anesthetic choice, for example, during propofol sedation, background population activity within the STN, as well as FR, was reduced [13,14,41,43,44,51], REMI combined with ketamine demonstrated a reduction in background activity with preserved neuronal FRs [45], and REMI alone had no effect [41].…”
Section: Discussionmentioning
confidence: 99%
“…Other centers reported symptomatic hemorrhage rates of SMER varying between 0.0% and 3.2%. 14,[16][17][18][22][23][24]27 An explanation for the reported difference in hemorrhagic complications between SMER and MER is the relatively blunt tip of the SMER. Another explanation may be the lower number of tracks needed during the insertion procedures, 9 which also reduces procedural time and costs.…”
Section: Discussionmentioning
confidence: 99%